2022
DOI: 10.3390/jmmp6050094
|View full text |Cite
|
Sign up to set email alerts
|

Fretting Fatigue as a Limiting Factor on the Durability of Friction Stir Welded Lap Joints Using AA2099-T83 and AA2060-T8E30 Aluminium Alloys

Abstract: Friction stir welding (FSW) has been proposed as an alternative modern joining technology and demonstrated important benefits for the manufacturing of efficient and lightweight aircraft structures using high-strength aluminium alloys. These structures are required to be corrosion- resistant and thus, it is necessary to use technologies such as surface treatments and sealants in their manufacturing and assembly. In this work, the feasibility of combining innovative Cr-free surface treatments, sealants and FSW t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Owing to its solid-state nature, FSW eliminates solidification defects, such as voids and cracks, and thus routinely produces sound joints in most aluminium alloys. This has created new opportunities for manufacturing more complex components from these alloys for various industrial applications, e.g., [2][3][4]. Specifically, FSW has been successfully deployed as an alternative to conventional fusion welding or riveting for the manufacturing of large-scale structures, such as aircraft fuselage skins, train cars, etc., in the transportation industry.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its solid-state nature, FSW eliminates solidification defects, such as voids and cracks, and thus routinely produces sound joints in most aluminium alloys. This has created new opportunities for manufacturing more complex components from these alloys for various industrial applications, e.g., [2][3][4]. Specifically, FSW has been successfully deployed as an alternative to conventional fusion welding or riveting for the manufacturing of large-scale structures, such as aircraft fuselage skins, train cars, etc., in the transportation industry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have reported that FSW of TFSAA or solgel-treated third-generation Al-Cu-Li aluminum alloys combined with sealant application at the crevice of the lap joints seems to be a feasible and promising technique for the manufacturing of lightweight aeronautic structures with good corrosion resistance [12]. In addition, sealant application has been reported to improve the mechanical performance of the stringer-skin FSW joints under loop stress loading conditions compared to joints with no sealant application [13].…”
Section: Introductionmentioning
confidence: 99%
“…FSW facilitates obtaining high-quality and low-cost joints. It is especially remarkable its use to weld heat treatable aluminum alloys which are difficult to weld by fusion welding technologies [24][25][26][27][28][29][30][31][32]. Moreover, FSW has been successfully employed to weld other materials such as steel, titanium, magnesium, copper, nickel or even composite materials [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%